Navigating Human Immunodeficiency Virus Screening Recommendations for People on Pre-Exposure Prophylaxis and the Need to Update Testing Algorithms. (15th April 2022) - Meyerowitz, Eric A; Bernardo, Raffaele M; Collins-Ogle, Michelle D; Czeresnia, Jonathan M; Matos, Cariane M; Mullis, Caroline; Root, Heather B; Torres-Isasiga, Julián A; Tsai, Helen; Zingman, Barry S
Abstract: Incident HIV infections occurring in people on PrEP may have delayed seroconversion. New CDC guidelines recommend the addition of HIV-1 viral load for screening for all on PrEP. We believe antigen/antibody screening should continue for tenofovir-based PrEP at this time. Abstract : Diagnosis of incident HIV infections occurring on PrEP may be delayed due to unpredictability of tests in this setting. Routine HIV-1 RNA screening, while appropriate, may not be necessary or practical for people on tenofovir formulations in the current context.